Mitochondrial morphology and synaptic structure altered in the retina of parkin-deficient mice. (1st November 2022) - Hu, Zheng-Xiang; Pu, Jia-Li; Zheng, Rong; Yan, Yi-Qun; Liu, Kai-Yuan; Liu, Yi; Zheng, Ran; Chen, Ying; Lin, Zhi-Hao; Xue, Nai-Jia; Li, Peng; Zhang, Bao-Rong
Highlights: Retinal structure altered in parkin–/– mice at early stage. Mitochondria of mito-5 decreased significantly in the OPL of parkin–/– mice. Mitochondria in the OPL were swollen severely in parkin–/– mice. Ribbons in RSs reduced in parkin–/– mice compared with control. RSs of parkin–/– mice were swollen severely with sparse vesicles after stimulation. Abstract: Mutations in the PRKN gene are the major cause of autosomal recessive Parkinson's disease (PD). However, studies of parkin–/– mice did not show the loss of dopaminergic neurons and motor phenotypes at a young age. Whether pathological changes are associated with nonmotor symptoms of PD remains unclear. Visual impairment is one common nonmotor symptom in patients with PD. This study aimed to examine the effects of parkin–/– on mitochondria and synaptic structures in the retina of 6-month-old mice. Compared with wild-type mice, parkin–/– mice exhibited a slightly thickened retina. Also, the number of normal mitochondria (mito-5 grade) in rod spherules (RSs) significantly decreased ( p  < 0.01), the average area of mitochondria was significantly larger ( p  < 0.001), and the number of ribbons in RSs significantly decreased ( p  = 0.02). The RSs of parkin–/– mice showed severe swelling after flicker stimulation. Our study implicated that parkin–/– led to the impairment of mitochondria and abnormality of the synaptic structure in mouse retina at a young age, which damaged the synaptic transmission between photoreceptors and second-order retinal neurons and resulted in visual impairment.